Knowledge capacity building through quality management of education and institutions of higher learning - Nirwan, Idrus (Assumption University of Thailand, 2006)
The globalization of knowledge or information is multidirectional. It only makes sense when the provider and recipient of the knowledge or information are capable of both providing and receiving. The fact currently is that this is not the case, especially when it involves developing countries. While the expectations are that developing countries should at least be able to receive, if not provide, the education infrastructure is normally not present to allow that to happen. This paper proposes an exploration into effective learning, a move away from current pedagogical thinking and delivery and instilling innovative management of institutions of higher learning, so that we could catch up with the rest of the world and hence join them in globalizing knowledge and information. In particular, this paper discusses the demise of rote learning in this technological and globalised world and challenges the Asian values concept of acceptance. In combating these educational drawbacks, this paper advocates a fundamental change in the requirements of teachers in the broadest sense of the word (i.e. including lecturers and professors). At the same time this paper also discusses the need for a conducive environment to allow the above to occur. This leads to a quality-based management of higher education institutions. This requirement has become a given in many developed countries.